Two new troglobitic species of Oxarthrius Reitter (Coleoptera, Staphylinidae, Pselaphinae) from Brazil - Asenjo, Angélico; Zampaulo, Robson De Almeida; Ferreira, Rodrigo Lopes (Zootaxa, 2018)
Two new species, Oxarthrius inexpectatus and Oxarthrius aurora, are described from caves in Minas Gerais and Tocantins states in Brazil, respectively. The major diagnostic features are illustrated and a key to the known species from Brazil is given.